Exploring and Understanding the Subjective Experiences of ‘Home’ Feeling Away Students Living In Hostel - Hafsa Khalid Awan; Dr Nida Nosheen; Noshaba Ajaz (Research Journal of Psychology, 2025)
Aim: This study explores the subjective experiences of students living in hostels and how they conceptualize 'home' away from family residences. Design: A qualitative, phenomenological design was utilized, employing reflexive thematic analysis. Methods: Data were collected through semi-structured interviews with eight hostel students selected via purposive sampling. Thematic analysis revealed ten key themes reflecting the social, emotional, and environmental dimensions of hostel living. Results: Major themes included emotional resilience, social dynamics, personalization efforts, and the psychological challenges of adjusting to hostel life. The findings emphasized the interplay between social bonds, cultural adaptation, and emotional well-being. Conclusion: Hostel life fosters personal growth and social development but is marked by challenges in creating a sense of 'home.' Future interventions should focus on enhancing environmental and emotional support to improve students' well-being.